2013
DOI: 10.1590/s0034-737x2013000500009
|View full text |Cite
|
Sign up to set email alerts
|

Estimação da área foliar por método não destrutivo, utilizando medidas lineares das folhas de espécies de Passiflora

Abstract: Estimation of leaf area by non-destructive method using linear measurements of leaves ofPassiflora speciesThe objective of the present study was to develop a reliable equation which enables a fast and non-destructive calculation of leaf area using linear leaf measures from different Passiflora species (P. alata, P. coccinea, P. gibertii, P. ligularis, P. misera, P. mucronata, P. nitida, P. setacea). Three hundred leaves with different sizes were collected from each species. It was performed the analysis of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 22 publications
2
20
0
11
Order By: Relevance
“…Similarly, Morgado et al (2013) reported high coefficients of determination in the generated models (≥ 0.772), and the product between the length and the greatest width was chosen to determine directly and easily the leaf area in lanceolate and trilobed leaves of wild Passiflora species. According to the authors, the leaf area is an important parameter in experimental studies of fruit crops because, according to Spann and Heerema (2010), it can influence photosynthesis, transpiration, and leaf expansion, and it affects the growth rate and the quality of production.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, Morgado et al (2013) reported high coefficients of determination in the generated models (≥ 0.772), and the product between the length and the greatest width was chosen to determine directly and easily the leaf area in lanceolate and trilobed leaves of wild Passiflora species. According to the authors, the leaf area is an important parameter in experimental studies of fruit crops because, according to Spann and Heerema (2010), it can influence photosynthesis, transpiration, and leaf expansion, and it affects the growth rate and the quality of production.…”
Section: Resultsmentioning
confidence: 99%
“…According to the authors, the leaf area is an important parameter in experimental studies of fruit crops because, according to Spann and Heerema (2010), it can influence photosynthesis, transpiration, and leaf expansion, and it affects the growth rate and the quality of production. With the validation of mathematical models using precise and accurate indices, the equations in the study can be used to measure the area of different morphological patterns of passion fruit leaves quickly, accurately and non-destructively, as also observed by Morgado et al (2013) in obtaining the leaf area of wild Passiflora species.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations